STUDI KETAHANAN ELEMEN STRUKTUR KOLOM GEDUNG PERKANTORAN DENGAN USIA LAYAN 40 TAHUN - Asiya Nurhasanah Habirun (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2023)
The service life of the structure and the addition of additional dead loads on the floor slabs have caused a decrease in the capacity of the slab and beam structural elements. The study on the column section was carried out to analyze the capacity under these conditions. Inspection and field testing are carried out to obtain the suitability of the column reinforcement installed on the as built drawings and the quality of the concrete surface with a hammer test. Field test results show that 80% of the columns have low concrete quality below 21 MPa. The column structure experienced a decrease in the bearing capacity of the structural elements based on the results of the analysis where the axial and flexural forces were outside the cross-sectional capacity in the interaction diagram.